Fixation for Osteochondral Lesions of the Talus with Open Lift, Drill, Fill and Fix (LDFF) Results in Excellent Two-Year Clinical Outcomes - Quinten Rikken MD; Jari Dahmen MD; Kaj Lambers MD, PhD; Sjoerd Stufkens MD, PhD; Gino M M.M.J. Kerkhoffs MD, PhD (Foot & Ankle Orthopaedics)
Category: Ankle Introduction/Purpose: Outcomes after fixation of osteochondral lesions of the talus (OLTs) are currently underreported in literature. Clinical and radiological outcomes after the open fixation procedure ‘lift-drill-fill-fix’ (LDFF) for OLT with an osteochondral fragment are unknown. The advantages of fixation over other surgical techniques is the preservation of the native hyaline cartilage, immediate stabilization of the fragment and restoration of the talar dome congruency, as well as facilitating subchondral bone healing. Methods: This study describes the results of open LDFF treatment in a prospective, multicentre, nonrandomized, noncomparative clinical trial of 42 ankles in 40 patients with a 2-year follow-up period. The primary outcome measure in this study was the numeric rating scale (NRS) of pain during walking. Secondary outcome measures included the NRS of pain during rest, running and stairclimbing, the foot and ankle outcome sore (FAOS), and the mental component scale (MCS) and physical component scale (PCS) of the short form 36 (SF-36), and the radiological union rate as well as the level of the subchondral bone layer as measured on 1-year postoperative CT. Results: A total of 40 ankles which underwent fixation of an OLT with a fragment were prospectively included with 2-years follow-up. The primary outcome, pain during walking, significantly improved with 3.5 (95% CI 2.4-4.6) points on the NRS (p=< 0.001). Significant improvement was also seen for the NRS of pain during rest (p=< 0.001), pain during running (p=< 0.001) and pain during stair climbing (p=< 0.001). Additionally, all subscales of the FAOS, and the MCS and PCS significantly improved as well. Postoperative CT-scans showed union in 88% of the lesions 1-year after the procedure, a flush subchondral bone layer in 88%, and a depressed subchondral bone layer in 12%. Conclusion: Open fixation by means of LDFF for OLT results in a significant improvement of clinical outcomes up-to mid-term follow-up. Radiological follow-up shows a union rate and a flush subchondral bone layer in 88% of lesions. These results indicate that open fixation should always be considered when an osteochondral fragment is present as it leads to an excellent improvement in PROMs.